Auditory processing parallels reading abilities in adults - Ahissar, Merav (National Academy of Sciences, 2000)
A broad battery of psychoacoustic measures and standard measures of reading and spelling were applied to 102 adults. The test group included individuals with a childhood history of reading difficulties and controls with no reported reading difficulties. Reading scores were variable in both groups. Poor auditory processing abilities were recorded in poor readers; particular difficulties were posed by tasks requiring spectral distinctions, the simplest of which was pure tone frequency discrimination. In absolute terms, the greatest deficits were recorded in tasks in which stimuli were presented in brief forms and in rapid succession. Auditory processing abilities accounted for more than 50% of the reading score variance in the control group, but their correlation with reading scores was lower in the group with childhood histories of reading difficulties. The additional variability in the latter group resulted largely from the prevalence of reading-compensated poor psychoacoustic performers, whose short-term word memory was also typically poor. Taken together, these findings support a link between impaired auditory resolution and poor reading. Psychoacoustic difficulties are largely retained through adulthood and may be the source of the retained reading difficulties.